Matematyka
gingerova
2017-06-26 17:33:57
Błagam o pomoc.. (4x-8)+(5x-6)= (4x-3)(2x+1)= -2(x-2)(4x+1)= (x+√7)*2= (x-3y)*2= (2/3-c)*2= 104(do kwadratu)
Odpowiedź
lisekchytrusek
2017-06-26 22:04:46

[latex](4x-8)+(5x-6)=4x-8+5x-6=9x-14 \ \ (4x-3)(2x+1)=8 x^{2} +4x-6x-3=8 x^{2} -2x-3 \ \ -2(x-2)(4x+1)=(-2x+4)(4x+1)=-8 x^{2} -2x+16x+4= \ =-8 x^{2} +14x+4 \ \ (x+ sqrt{7} )*2=2x+2 sqrt{7} \ \ (x-3y)*2=2x-6y \ \ ( frac{2}{3} -c)*2= frac{4}{3} -2c \ \ 104 ^{2} =104*104=10816[/latex]

Dodaj swoją odpowiedź